The characteristic’s impact on environment of laminated product’s plants - Nahurskyy, О.; Tsyhaniuk, S. (Lviv Polytechnic Publishing House, 2015)
We developed an ecological estimation of the influence of production on the environment. The methods of cleaning of the polluted gaseous environment were analyzed as well as the technological 4-stage plan of cleaning the flue gas from the coal ashes and SO2 was proposed.
Keywords: ecology; lamination; gas environment; environment; flue gases; coal ash; SO2